CHARACTER EDUCATION THROUGH ITS DEPICTION OF LIFE IN THE NOVEL ENTITLED KERUMUNAN TERAKHIR BY OKKY MADASARI (PSYCHOLOGYCAL ANALYSIS OF LITERATURE) - Devilito, Rio; Wardani, Nugraheni Eko; Saddhono, Kundharu (English Department FBS UNP, 2017)
This paper aims to describe (1) psycological conflict experienced by the main character; (2) psycological symtomps affecting in behavior aspect of main character to solve the problem of life; (3) the value of characterized-education in the novel entitled Kerumunan Terakhir which is relevant as a material of Indonesian learning. The method used in this research is descriptive qualitative based on descriptive data that has been found in the research. The main source of data in the research is about the quotation contained in the novel and the interview result with the literature expert. The result of study is about relevance of Kerumunan Terakhir with the learning of Indonesian and character education based on problem whom experienced by main chracter in novel.Â